Black Lives Matter and Mães de Maio: What Unites Us - Gregis Estivalet, Anelise (Frontiers in Sociology, 2022)
The long history of slavery in the USA and Brazil is still evident when looking at the violence which takes place in each country today. In addition, the growing militarization of public management is due to the foreign policy of the USA and the military dictatorship of Brazil which lasted more than 30 years. Facing situations of violence, mainly state-owned, the 1970s were marked by women's resistance and struggle against violence, authoritarianism and lack of citizenship, particularly in Latin America. These social movements represented the distancing of ideology as an engine of social mobilizations, as well as the conversion of collective identity policies into generators of responses. The ability to form a collective identity around the common identification of oppression allowed the development of these new mass movements. From the construction of a collective female identity, intimate and personal aspects gained a central dimension in the identification of oppression, consequently, in the project of personal and social transformation. The agendas of this second wave of the feminist movement encompassed both the struggle for civil rights and the rights of blacks, pacifist, student and decolonization movements. Considering the influence of these new feminist movements on two current social movements, namely "Black Lives Matter" (United States) and "Mães de Maio" (Brazil), I want to understand, in this article, how the guiding meanings of gender, race, sexuality, class and generation, present in the third and fourth waves of feminists, appear in practice, in these two social movements that have the same generative facts as triggers for their constitution.